Violation of Exclusive Distribution Agreement: Case Study of PT Unilever Indonesia Tbk vs PT Indomarco Prismatama - Yuwono, Lila Graciella; Lie, Gunardi (CV. Rayyan Dwi Bharata, 2024)
Breach of exclusive distribution agreement is one of the critical issues that often arise in business relationships between manufacturers and distributors, especially in competitive industries such as fast-moving consumer goods. The case involving PT Unilever Indonesia Tbk and PT Indomarco Prismatama (Indomaret) is a clear example of such a dispute, where the dispute arose from an alleged breach of an exclusive distribution agreement by Indomaret. Unilever claimed that Indomaret, acting as one of their main distributors, had sold Unilever's products outside the terms stipulated in the exclusive agreement, including selling the products below the agreed price or even to third parties not included in the authorized distribution network. This study examines in depth the legal aspects of exclusive distribution agreements in the context of business disputes in Indonesia, with a focus on the Supreme Court's decision number 1559 K/Pdt/2015 which upheld Unilever's claim for breach of contract by Indomaret. Through normative juridical analysis, this research seeks to explore the implications of the ruling for product distribution practices in Indonesia, as well as how such breaches may affect the long-term business relationship between manufacturers and distributors. The analysis shows that exclusive distribution agreements are contractual instruments that have a significant impact on competition in the market. When one party breaches the agreed terms, whether in terms of price, distribution area, or other requirements, the impact is not only limited to legal aspects, but also touches on aspects of reputation and business relationships. In this case, the Supreme Court ruled that PT Indomarco Prismatama was guilty of breach of contract and was required to compensate PT Unilever Indonesia Tbk. This judgment emphasizes the importance of compliance with exclusive distribution contracts and the need for strict sanctions to maintain market integrity. The broader impact of this breach also includes aspects of fair competition. This research highlights how non-compliant distribution practices can affect market dynamics, especially when large distributors such as Indomaret are involved. Under these conditions, exclusive distribution violations can create unfair conditions for other business actors who operate in accordance with existing rules. Therefore, in addition to the legal implications of breach of contract, this study also proposes stricter regulations and effective monitoring mechanisms to prevent such practices from occurring in the future. In addition, this study also provides insights into how the business relationship between producers and distributors should be maintained through a clear and transparent contractual mechanism. One of the key findings of this research is the importance of detailed agreements and strict sanctions against violations, as well as the need for close supervision of contract implementation, especially in highly competitive industries. This applies not only to the consumer goods sector, but also to other sectors that rely on extensive and complex distribution systems. Thus, this research contributes to the understanding of the importance of exclusive distribution agreements in maintaining a balance between the business interests of producers and distributors, as well as in ensuring the creation of a competitive and fair business climate. This research also enriches the literature on business and distribution law in Indonesia, and provides practical insights for companies involved in distribution agreements to avoid potential disputes in the future.